2018
DOI: 10.1186/s12964-018-0216-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR promotes cell migration and invasion by regulating MKL1 via inhibition miR206 expression in HeLa cells

Abstract: BackgroundLong non-coding RNAs (lncRNAs) have emerged as a new and crucial layer of gene regulation in recent years and regulate various biological processes such as carcinogenesis and metastasis. LncRNA HOTAIR, an oncogenic lncRNA, is involved in human tumorigenesis and dysregulated in cervical cancer. Megakaryoblastic leukemia 1 (MKL1), as a transcription coactivity factor, involved in cancer metastasis and cell differentiation. However, the precise mechanism of biological roles of HOTAIR and MKL1 in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 74 publications
3
34
0
Order By: Relevance
“…RIF is commonly regarded as the final outcome of a majority of progressive CKDs, in which fibrosis is a consequence of a gradual increase in myofibroblasts concentration in the renal interstitial space . In recent years, lncRNAs have been proven to critically function in the development of fibrosis of various diseases such as cardiac interstitial fibrosis and lung interstitial fibrosis (Cao et al, 2013;Liang et al, 2018 Besides, accumulating findings have highlighted the ability of lncRNA HOTAIR to enhance the migration of a various types of cells such as HeLa cells and breast cancer cells (Zhao, Geng, Li, Chen, & Sun, 2018; P. Zheng, Yin, et al, 2018). Existing evidence has remarked that lncRNAs could enhance EMT of idiopathic pulmonary fibrosis by regulating the expression of genes involved in EMT (Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…RIF is commonly regarded as the final outcome of a majority of progressive CKDs, in which fibrosis is a consequence of a gradual increase in myofibroblasts concentration in the renal interstitial space . In recent years, lncRNAs have been proven to critically function in the development of fibrosis of various diseases such as cardiac interstitial fibrosis and lung interstitial fibrosis (Cao et al, 2013;Liang et al, 2018 Besides, accumulating findings have highlighted the ability of lncRNA HOTAIR to enhance the migration of a various types of cells such as HeLa cells and breast cancer cells (Zhao, Geng, Li, Chen, & Sun, 2018; P. Zheng, Yin, et al, 2018). Existing evidence has remarked that lncRNAs could enhance EMT of idiopathic pulmonary fibrosis by regulating the expression of genes involved in EMT (Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies document that lncRNAs are essential regulator in various biological processes ( 18 20 ). In human cancer, lncRNAs have been demonstrated to serve pivotal roles in regulating cellular proliferation, apoptosis, migration and invasion ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that lncRNA exerts a crucial role in role in the development process, genomic imprinting, cellular homeostasis, and pluripotency of embryonic stem cells (7)(8)(9). Generally, the abnormally expressed lncRNAs participate in many biological mechanisms at the epigenetic, transcriptional, and posttranscriptional levels (10)(11)(12), such as cell proliferation, metabolism, apoptosis, migration and differentiation (13)(14)(15). Recently, a new regulatory mechanism indicates that the potential effect of lncRNAs is to inhibit the expression and biological functions of miRNAs(microRNA) as competing endogenous RNAs (ceRNA) (16,17).…”
Section: Introductionmentioning
confidence: 99%